Analysis of the Influence of WOM, Physical Environment and School Image on the Decision to Choose a School with Intention to Choose a School as a Mediating Variable (Study on Students of SMKN 47 Jakarta) - Miftahul Huda; Adi Nurmahdi (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to determine and analyze the influence of word of mouth, physical environment and school image on the decision to choose a school with the intensity of choosing a school as a mediating variable (a study on students of SMKN 47 Jakarta). The population used in this study were students enrolled at SMKN 47 Jakarta in the 2024/2025 academic year. The method used in this study was probability sampling with a simple random sampling technique, with the criteria being students of SMKN 47 Jakarta enrolled in the 2024-2025 academic year, with a sample size of 187 respondents. The data analysis method used Structural Equation Model-Partial Least Square (SEM-PLS). The results of this study indicate that word of mouth and the physical environment have a positive and significant influence on the intensity of choosing, while the image of the school does not have a significant influence on the intensity of choosing. Word of mouth, the physical environment and the image of the school and the intensity of choosing have a positive and significant influence on the decision to choose a school. The intention to choose is a partial mediation between word of mouth and the physical environment on the decision to choose a school, while there is no mediation on the image of the school.